1976
DOI: 10.1677/joe.0.0690427
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Weight of the Adrenal Glands and in the Concentration of Plasma Corticosterone in Perinatal Rats After Prenatal Treatment With Oestradiol Benzoate

Abstract: On day 20 of gestation, foetal rats received a subcutaneous injection of 0-01 mg oestradiol benzoate dissolved in 0-05 ml sesame oil; foetuses in other litters were given sesame oil alone. Autopsy was performed on day 22 of gestation, at delivery or at various times after birth. Gravimetric and histological observations of the adrenals from oestradiol-treated, oil-treated and intact litter-mate control foetal and neonatal rats were performed together with determination of plasma corticosterone concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
(10 reference statements)
2
3
0
Order By: Relevance
“…That the adrenal glands of the newborn rat are activated at birth is suggested by the high levels of circulating corticosterone and the sub sequent decrease until 8 h. Our results are in good agreement with those of Eguchi et al (11), who found that the plasma corticosterone concentration increased during delivery of rat fetuses, reaching a maximum about 2 h after birth and then decreasing gradually until 12 h.…”
Section: Plasma Corticosteronesupporting
confidence: 93%
See 2 more Smart Citations
“…That the adrenal glands of the newborn rat are activated at birth is suggested by the high levels of circulating corticosterone and the sub sequent decrease until 8 h. Our results are in good agreement with those of Eguchi et al (11), who found that the plasma corticosterone concentration increased during delivery of rat fetuses, reaching a maximum about 2 h after birth and then decreasing gradually until 12 h.…”
Section: Plasma Corticosteronesupporting
confidence: 93%
“…A slight increase during the last hours of in trauterine life is followed by a rapid decrease between hours 2 and 4. These results are con sistent with previous data on the decrease of adrenal weight between birth and the first 2 days of life (4,7,11). The adrenals have a hyperhemic appearance at birth whichdisappears by 4 h, suggesting that the glands were strongly stimulated.…”
Section: Adrenal Weightsupporting
confidence: 91%
See 1 more Smart Citation
“…(Josimovich et al, 1954;Cohen, 1959;Eguchi and Ariyuki, 1963). This reduction is not absolutely due to the absence of maternal ACTH (see review by Eguchi, 1969), but seemingly due to a blockade of the newborn pituitary by a markedly high level of plasma corticosterone which occurs at and just after delivery (Eguchi et al, 1976). Estradiol benzoate, when given prenatally, prevents both an extreme increase in the concentration of plasma corticosterone at and just after birth and a decline of the weight of neonatal adrenals (Eguchi et al, 1976).…”
mentioning
confidence: 99%
“…or to the hypothalamic CRF mobilized by the METimposed reduction of corticosterone levels in circulation. Similarly, Eguchi et al [6] have suggested that the pituitary is very sensitive to circulating corticosteroids in perinatal life. The results obtained in the present study may, at least partly, be ascribed to the slower degradation and inactivation of MET in 5-than in 10-day-old rats.…”
Section: Discussionmentioning
confidence: 87%